Water extract have superior cytotoxic effect than ethanolic extract of clinacanthus nutans leaves in breast cancer stem cells - Syarifah, Siti; Rambe, Aldy S.; Putra, Agung; Ichwan, M; Pane, Yunita Sari; Muhar, Adi Muradi; Khatib, Alfi; Munir, Delfitri; Rusda, M; Amin, Mustafa (Avicena Publishing, 2024)
Background: The rapid development of medical technology in managing breast cancer patients still cannot solve the problem of recurrence and resistance. One of the causes of recurrence and molecular resistance is the presence of breast cancer stem cells (BCSCs). Clinacanthus nutans (C.nutans) is a plant found in Medan, North Sumatra, Indonesia. This plant is believed to have anticancer activity in community. Objective: Our study aimed to assess phytochemical of C.nutans leaves, isolate breast cancer stem cells and determine the cytotoxic effects of the ethanolic extract and water extract of C.nutans leaves on breast cancer stem cells at 24, 48, and 72 h of observation. Methods: We underwent the cytotoxic test by using MTT assay and isolated breast cancer stem cells by using MACS and validated them by mammosphere test. Results: We found alkaloids, flavonoids, glycosides and tannins in simplicia and all extracts. BCSCs was valid with the diameter of the mammosphere BCSCs was > 60 µm. The IC50 values of 100%, 60%, 40%, 20% EE, and WE of C.nutans leaves were 227.30; 46.05; 31.12; 98.54, and 16.16 µg/ml respectively in the first 24 hours. In administering WE of C.nutans leaves, BCSCs viability was decreased at 24,48 and 72 hours of observation, namely 69.29±26%; 75.82 ± 21.02% and 38.94±9.34 % (p < 0.0001). Conclusion: The WE of C.nutans leaves had more substantial cytotoxic potential against BCSCs than the EE. The capability of WE C.nutans leaves to suppress BCSC’s viability was time-dependent. The anticancer activity were believed originate from alkaloid and flavonoid group.